Savings and the informal sector. Issue 2 (3rd March 2020) - Dobson, Stephen; Ramlogan-Dobson, Carlyn; Strobl, Eric
ABSTRACT: In many countries the informal sector is a vital source of employment and income. But little is known about the impact of this sector on savings, which are crucial in promoting investment and growth. This paper finds an inverse relationship between savings rates and the informal sector when the informal sector is small. Once the informal sector reaches a certain size, further growth in the size of the informal sector boosts savings rates. The non-linear relationship is confirmed in both parametric and semi-parametric estimations. Rather than allowing the informal sector to grow unchecked, policy should focus on removing barriers for successful operation of business in the formal sector.